ECART / ASARECA / CTA Workshop On Impact Assessment of Agricultural Research in Eastern and Central Africa: Executive Summary - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
ASARECA, ECART and CTA have organised this regional workshop in order to improve the implementation of impact assessment in Eastern and Central Africa, and to strengthen partnerships between institutions in the ASARECA region and in Europe.